ANALYSIS OF THE INFLUENCE OF BASIN GEOLOGICAL CONDITIONS ON ROCK GEOCHEMICAL CHARACTERIZATION - Zahra, Zaizafun
Indonesia is a region with numerous sedimentary basins due to its geographical location. Each basin has different geological conditions, resulting diverse geochemical characteristics of the rocks. This study aims to analyze the influence of the geological condition of the basin on the geochemical characterization of the rocks. The geochemical characterization of the rocks was conducted based on static and kinetic tests on the samples from the Barito Basin and the Kutai Basin. The results indicate that the geological conditions influencing the geochemical characterization of the rocks are paleoclimate and paleodepositional environments. The Kutai Basin, which was formed under arid climatic conditions, produced rocks with a higher total sulfur content compared to the Barito Basin, which was formed under varying climatic conditions ranging from dry to humid. Furthermore, the Barito Basin was formed in an oxic depositional environment characterized by shallow marine conditions, whereas the Kutai Basin was formed in an anoxic depositional environment, including deltaic and marine settings. Consequently, carbonate content is higher in the Barito Basin, as indicated by the greater presence of NAF (Non-Acid Forming) rocks, while the Kutai Basin has higher occurrence of PAF (Potentially Acid Forming) rocks. Additionally, in the Barito Basin, depth affects the carbonate mineral content of the rocks, where the deeper the rock, the lower the ANC (Acid Neutralizing Capacity) value, indicating a lesser carbonate mineral content.